Underwater oblique shock wave reflection from submerged hydraulic structures. (1st August 2020) - Ghoshal, R.; Mitra, N.
Abstract: This paper investigates the effect of obliquity on impulse imparted to the hydraulic structures by an underwater shock wave. In this regard, the oblique shock reflection phenomenon due to a planar shock wave impingement on an inclined rigid surface is numerically modeled. Results from simulations are presented in this manuscript for different shock strengths and angles of structure obliquity. The study reveals that impulse transmitted to the structure due to oblique shock reflection is lower than that of normal incidence. In specific regimes of structure obliquity to incident shock direction, the formation of Mach-stem is observed, i.e., triple point configuration at a certain distance from the structure. Inside these regimes, the stem height decreases with the increase in structure obliquity and vice versa. Locus of the triple point has a direct implication on the magnitude of transmitted impulse, which reduces with the increase in stem height, i.e., more the locus of the triple point is away from the structure, less is the transmitted impulse. Results presented in this manuscript may help in understanding the physics of shock reflections from submerged hydraulic structures and subsequently framing mitigation strategies. Highlights: Underwater oblique shock reflection from on an inclined rigid surface is numerically modeled. Impulse transmission due to oblique reflection is lower than that of normal incidence. Increase in structural obliquity reduces the stem height but increases transmitted impulse. More the locus of the triple point is away from the structure less is the transmitted impulse. Obliquity in underwater structures may be effective in reducing impulse transmission.